PENGARUH PEMEDIASIAN KOMITMEN ORGANISASIONAL DALAM HUBUNGAN ANTARA KEPUASAN KERJA DAN INTENT TO LEAVE Studi pada Rumah Sakit di Yogyakarta - Siswanti, Yuni (Universitas Muhammadiyah Surakarta, 2006)
The purpose of this research is to examine the influence of organizational commitment as mediatingvariableÂ inÂ relation betweenÂ job satisfactionÂ and intenttoÂ leave. TheÂ samplesÂ wereÂ nursesÂ thoseÂ workingat DKT,Â Panti Rapih,Â Bethesda, andÂ PKU MuhammadiyahÂ hospitalâsÂ in Jogjakarta.Â Of the 126 questionnairesÂ wereÂ distributedÂ to theÂ nurses, 107 dataÂ thatÂ can employÂ onÂ this study.TheÂ data were collected use 4-item job satisfaction, 6-itemÂ for each threeÂ dimension organizational commitment, 3-itemintnt to leave. The overallÂ instruments those used inÂ this studyÂ wereÂ perceptive instruments.SimpleÂ regressionÂ analysis wasÂ used to examinethe influenceÂ independentÂ variable todependent variable.RegressionÂ analysis (BallonÂ and KennyÂ Modelâs) wasusedÂ to examineÂ whether organizational commitmentbecomeÂ mediatingÂ variableÂ in relationbetween jobÂ satisfaction andÂ intent to leave.